(untitled) (Orthodontic Journal of Nepal, 2021)
Introduction: Balance in vertical facial proportion is an important criteria for good esthetics. Variations in vertical growth are common and have certain orthodontic implications. The objectives of this study were to determine mean upper anterior facial height and lower anterior facial height, ratio between UAFH to LAFH and their difference among genders in skeletal Class I patients with different vertical growth pattern among patients visiting department of Orthodontic and Dentofacial orthopedics, Tribhuvan University Dental Teaching Hospital, Kathmandu. Materials and Method: This study was descriptive observational cross sectional study with 105 sample aged from 18-25 years. Pretreatment cephalometric radiograph of Skeletal Class I patients were taken and divided into three growth patterns as group I (normal growth pattern), group II (horizontal growth pattern ) and group III (vertical growth pattern ). Upper anterior facial height (N-ANS) and lower anterior facial height (ANS-Me) of all samples were measured on lateral cephalogram with cephalometric tracing ruler parallel to true vertical line. Descriptive statistics was used to calculate mean, minimum, and maximum values standard deviations with p value <0.05. Result: The upper anterior facial height (UAFH) and lower anterior facial height (LAFH) measurements in normal growth pattern was 52.37 and 64.4 , in horizontal growth pattern was 53.0 and 62.2, in vertical growth pattern was 53.37 and 64.42 respectively. The mean ratio of upper and lower anterior facial height in normal, horizontal and vertical growth pattern was 0.81, 0.85 and 0.79 respectively. There was no statistically significant difference in upper and lower facial heights between males and females. There was no statistically significant difference in UAFH between normal, horizontal and vertical growth pattern but statistically significant difference was observed in LAFH between groups. Conclusion: The cephalometric values for different vertical groups in skeletal class I can be used more specifically for diagnosis and treatment planning of Nepali population.